SOCIAL INTERACTION OF BUGIS WOMEN IN THE CULTURE OF SIRI’ NA PESSE IN MAKASSAR - Rifai, A Fadhilah Utami Ilma (Walasuji : Jurnal Sejarah dan Budaya, 2021)
This study aimed to show the social interactions that occured in Bugis women with culture of Siri' na Pesse as a culture that is still being respected today in Makassar City. The main problem examined the implementation of the culture of Siri’ by Bugis young generation who live in Makassar City in their daily lives when they are interacting in society. Siri' is the basic value possessed by each individual and it is hereditary. In interacting with each other, either with Bugis or with other tribes in Bugis society, they always instill the value of Siri 'na Pesse. From the past, anything could be done in upholding Siri' values in society. Therefore, this study described the implementation of the culture of Siri’ by the young generation in their daily lives when interacting in their association in Makassar City.